TINJAUAN HUKUM ISLAM TERHADAP PENERAPAN METODE ANNUITAS DALAM PEMBIAYAAN MURᾹBAHAH DI PERBANKAN SYARIAH (Studi Kasus di Bank Syariah Mandiri Kantor Cabang Kebonjeruk) - Setiya Afandi (Madani Syari'ah: Jurnal Pemikiran Perbankan Syariah, 2019)
West Jakarta Kebonjeruk Branch Office of Bank Syariah Mandiri uses annuity method in determining its profit. Such method is considered a burden by the customers. By the time customers complete the installment exactly at the half financing term some provisions applied, consequently increases the additional cost. Such cost is applied because West Jakarta Kebonjeruk Branch Office of Bank Syariah Mandiri takes profit in the beginning of financing scheme whereas the installments are charged more in the end part if the scheme. Thus, the practice has clearly shown that West Jakarta Kebonjeruk Branch Office of Bank Syariah Mandiri unfairly treats customers. Additionally, such practice is not in line with Islamic law.